Murici (Byrsonima verbascifolia): A high bioactive potential fruit for application in cereal bars. (15th April 2022) - de Barros Vinhal, Gabrielle Lázara Ribeiro Rodrigues; Ribeiro Sanches, Marcio Augusto; Barcia, Milene Teixeira; Rodrigues, Daniele; Pertuzatti, Paula Becker
Abstract: In order to popularize and use murici fruit ( Byrsonima verbascifolia ) in processed foods, the aim of the study was to characterize the fresh fruit as to its antioxidant capacity, volatile and bioactive compounds and to evaluate the effect of murici content on total carotenoids and sensory attributes in enriched cereal bars. For the development of cereal bars, a Plackett-Burman design was elaborated, containing eight independent variables: glucose syrup, oats in thick flakes, corn flakes, rice flakes, dehydrated murici, soy lecithin, hydrogenated vegetable fat, and brown sugar. Fresh murici were characterized for proximate composition, total and individual carotenoids, antioxidant capacity, volatile compounds, and microbiological analysis. The murici was mainly a good source of fiber (6.4%) and lipids (7.3%), with significant levels of total carotenoids (15.3 μg of β-carotene/g) and antioxidant capacity by FRAP method and ABTS method. The volatile fraction of murici mainly contains esters with descriptors such as cheese and fruity. The experimental design used helped obtain the formulations of cereal bars with murici and demonstrated that the content of carotenoids increases as the amount of added fruit increases. Highlights: Twelve volatile components were found and identified in fresh murici. Murici volatile fraction contains esters with descriptors such as cheese and fruity. Antioxidant capacity increased after dehydration of murici. The main carotenoids present in fresh murici were lutein and β-carotene. The content of carotenoids increases with the increase of murici in cereal bars.